The Effectiveness of a Senior High School English Immersion Program on Graduates Communicative Competence and Academic Achievement in Higher Education - Hateenah Ali Sulaiman Yousef; M Muamaroh; Agus Wijayanto; Nur Hidayat; Anam Sutopo; Abdillah Nugroho; Dwi Haryanti (Universitas Muhammadiyah Surakarta, 2025)
Purpose: The purpose of this investigation is to explore the impact of Artificial Intelligence (AI) in English language education, focusing on teachers' perspectives on the positive and negative aspects of implementing AI in EFL classrooms; ways in which AI supports teachers' instructional practices, engages students in learning, and impacts teachers’ own pedagogical practices in addition to the ethical and professional implications of its use.Methodology: This study utilized a descriptive qualitative research methodology. The data were obtained through twelve semi-structured interviews with English language teachers working at one of the private universities in the English department in Indonesia. The participants were intentionally sampled based on their exposure to AI-supported instructional tools. The qualitative data were then analysed thematically to investigate the perceptions teachers had based on recurring themes and categories related to their experiences, challenges, and reflections about AI in education.Results: The findings indicated that AI offers remarkable advantages, including increased teaching efficiency, personalized support for learners, and heightened student motivation. However, the study identified several challenges, including limitations in teacher training, ethical implications related to data collection, technological constraints, and a potential reduction in human interaction. The findings suggest that the effectiveness of AI integration relies not only on teachers but also on administrators, policies, and ethical positions. Applications/Originality/Value: This research sheds light on the human-centered use of AI in language education. Utilizing Humanistic Learning Theory and the TPACK framework, it demonstrates how teachers can uphold empathy, authenticity, and pedagogical balance in the wake of emerging technology. These insights matter for policy design and professional development of eco-sustainable practices for using AI-enhanced instruction.